Prediction of weightlifter`s motor behavior to evaluate snatch weightlifting techniques based on a new method of investigation of consumed energy - Rahmati, S.M.A.; Mallakzadeh, M. (Human Movement Science, 2014)
Using proper technique in different sports is an inevitable factor. In this study, available techniques for snatch weightlifting are mathematically evaluated. The optimal motion trajectory is a technique used by weightlifters, which could be determined based on minimizing specific object functions. Object functions based on total kinetic energy, total torque and total power and some new multiobjective functions are minimized using genetic algorithm and the minimax principle. Some important motion characteristics of 13 professional weightlifters were extracted and used to validate the mathematical results. The double knee bending (DKB) technique was studied as a benchmark test. Some important movement features of the technique were shown by the mathematical analysis when applying an object function, that minimized joint torques and powers of different muscles independently. An object function based on joint forces did not show these features.